Finacial management - Brockington, Raymond B. (Eastleigh, Hants: DP Publications, 1993)
Intended for students preparing to take examinations on financial management at final professional level and it provides them with the knowledge and the skill that they need to pass.
Includes index.
ucj 06/11/2018
Loans
Keywords: Financial management